Heavy metal pollution decreases the stability of microbial co-occurrence networks in the rhizosphere of native plants - Sun, Caili; Wu, Pan; Wang, Guanghao; Kong, Xingjie (Frontiers in Environmental Science, 2022)
Soil microorganisms play an important role in maintaining soil quality and function, although the response of soil microbial biodiversity to heavy metals has been extensively investigated, the microbe-microbe associations under the influence of both native plant species and extremely high heavy metal contamination are not well documented. We examined the diversity and composition of microbial communities and the physicochemical properties in the rhizosphere of three native plant species, Carex breviculmis, Buddleja davidii, and Artemisia annua growing on and around a Pb-Zn waste heap with a nearly 100-year history of natural recovery. Both plant species and heavy metals influence soil microbial diversity and composition. C. breviculmis and A. annua showed a prominent advantage in increasing rhizosphere microbial diversity and richness as well as network complexity compared with plant Buddleja davidii at severely contaminated soil, which was mainly related to the accumulation of soil nutrients such as SOC, TN, NN and AN, rather than a reduction in heavy metal concentrations. Moreover, the heavy metal concentration and soil nutrient levels significantly affected the microbial groups affiliated with Proteobacteria, Chloroflexi, Ascomycota, and Basidiomycota, in which those affiliated with Chloroflexi and Ascomycota were positively associated with heavy metals. Soil microbial network on the Pb-Zn waste heap exhibited higher average degree and a higher proportion of positive links than those around the waste heap, indicating that soil microbial structure became more complexity and unstable with increasing heavy metal pollution. These findings promote a better understanding of the interaction among plants, heavy metals, and microbial communities on heavy metal-contaminated soils.